The Role of Technology in English Language Instruction at Islamic University: A Review of Strategies and Challenges - Hasibuan, Kalayo; Arianti, Yumna; Azzahra, Zuhudiah (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
The integration of technology in education has transformed teaching and learning processes worldwide, including English language instruction. This article examines the use of technology in English instruction at Islamic universities, focusing on strategies employed and challenges faced. The study highlights the advantages of tools such as Learning Management Systems (LMS), language learning applications, and blended learning models. Furthermore, it explores issues like digital literacy, technological infrastructure, and cultural and religious sensitivities. The findings underscore the importance of professional development for educators and the need for culturally sensitive content. By analyzing theoretical and practical perspectives, this research provides recommendations for improving technology adoption in Islamic academic settings. The conclusion suggests policies to enhance faculty training, infrastructure development, and the ethical use of technology.